Efeito de óleos essenciais sobre o desenvolvimento de Aspergillus ochraceus e Aspergillus carbonarius e na síntese de ocratoxina A - Nery, Abiah Narumy Ido de Abreu e (2015)
The presence of ochratoxin A in foods is considered quite disturbing by its effects, especially the nephrotoxic effects, and is potentially carcinogenic. Some fungi, such as Aspergillus carbonarius and Aspergillus ochraceus, are capable of producing this mycotoxin, mainly during storage period. To control these contaminants, the use of fungicides is quite common. However, consumers concern has risen regarding the excessive use of these compounds. Therefore, the use of natural substances, such as essential oils, as an alternative, has been extensively studied. The objective of this study was to evaluate the inhibition of OTA production by Aspergillus carbonarius and A. ochraceus, using different essential oils, in different forms of exposure and at different temperatures. We used six fungi, obtained from the culture collection of microorganisms from the Department of Food Science at the Universidade Federal de Lavras (UFLA), three A. carbonarius (CCDCA 01144, 01120 CCDCA, CCDCA 0128) and three Aspergillus Ochraceus (CCDCA 0167, CCDCA 0151, CCDCA 0153). An assessment of the minimum inhibitory concentration (MIC) was performed with five oils (Cymbopogon citratus; Syzygium aromaticum; Siparuna guianensis; Origanum vulgare, and Thymus vulgaris). From these analyzes, we selected three oils and four fungi for the next stages. Subsequently, mycelial growth was measured for 10 days at temperatures of 15.25 and 35°C. A test was conducted with agar diffusion and other volatile compounds. Samples that showed growth were subjected to HPLC to quantify OTA. Temperature influenced both growth and production of OTA. The MIC evaluated were insufficient for total inhibition of OTA production, mainly due to the exposure to volatile compounds. We also observed that exposure to low concentrations of these essential oils causes a significant increase in the production of OTA.